Factors that influence generation Y’s cinematic experience towards the selection of cinema in Malaysia - Yong, Josephine Pui Mun; Lau, Shirley; Lim, Nesylia E-Yun; Yap, Chung Sheng (2017)
The cinema and movies entertainment industry play an important role in providing moviegoers the means of escapism from the daily hustle and bustle. As Generation Y’s are entering into their prime spending years with extensive viewing habits, cinema operators need to be well-equipped with good products and services to prevent customers from losing interest in cinema entertainment. Hence, the main concern of cinema entertainment companies would always be enriching moviegoer’s boundless cinematic experience to enormously conserve loyal customers. Customer’s delightfulness of being more than satisfied towards the company’s services and retaining loyal customers tend to be more essential in reflecting a company’s profit and sustainability. Thus, this generates the attention of researchers to investigate the key factors that affect Generation Y’s cinematic experience towards the selection of cinema in Malaysia. As such, the main purpose of this study aims to determine the significant factors that influence Generation Y’s cinematic experience towards the selection of cinema in Malaysia. The data for this study was collected by using 200 forms of printed survey questionnaires which were distributed personally in random to 200 moviegoers from GSC, TGV, MBO and LFS cinemas. The version of 23rd Statistical Package for Social Sciences (SPSS) is being utilized to analyze the data collected from the printed survey questionnaires in this study. In addition, a few recommendations are presented to propose beneficial suggestions and call for further studies in this field.